Pengaruh Online Customer Review Terhadap Mahasiswa dalam Keputusan Pembelian Produk (Studi Kasus: Mahasiswa Ulbi Pengguna Shopee ) - Oriza Sativa Ma’ruf; Erik Saepuloh; Iwan Setiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of e-commerce and the internet requires business actors to be able to adapt, including in terms of marketing. Word of Mouth is a marketing strategy that is considered quite effective because it refers to human-to-human interaction through personal recommendations and positive experiences with something. In this era of social media, Online Customer Reviews are a form of evolution of Word of Mouth marketing. Online Customer Reviews utilize the power of Word of Mouth through digital platforms and have a significant impact in influencing consumer perceptions and purchasing decisions. This research uses several statistical tests to measure the reliability of the instruments and data. This research focuses on calculating the relationship between the Online Customer Review (X) and Purchase Decision (Y) variables at Shopee. The analysis results show a positive and significant correlation between the two, confirmed by simple linear regression and correlation tests. The findings confirm that Online Customer Reviews have a positive and significant influence on Consumer Purchasing Decisions. Therefore, sellers, especially on the Shopee marketplace, are expected to prioritize the quality of their products and services so that they can trigger good online customer reviews which then have an impact on increasing sales.